Increasing market share at Genelan Sdn. Bhd. - Wong, Foong Yee; Mohamed, Zainal Abidin; Chee, Suan Kim (Universiti Putra Malaysia Press, 2009)
Established in 1993, Geneland Sdn. Bhd. is a distributor of European life science products in Malaysia. Although the company’s total sales and profitability have been increasingly yearly, sales of company’s four main product types however still lag behind its two main competitors; Vision Sdn. Bhd. and Bio Science Sdn. Bhd. In order to enhance the competitiveness of the company, the CEO of the company instructed its General Manager to formulate a marketing plan to evaluate the company’s current products, the needs of its customers as well as to do a sales analysis in the context of a competitive industry in life sciences products.